Effectiveness of curcumin mouthwash on radiation-induced oral mucositis among head and neck cancer patients: A triple-blind, pilot randomised controlled trial - Swikant Shah; Hemamalini Rath; Gaurav Sharma; Surendra Nath Senapati; Ekagrata Mishra (Wolters Kluwer Medknow Publications, 2020)
Introduction: Radiation-induced oral mucositis (RIOM) is considered the most severe non-haematological complication affecting almost every head and neck cancer patient during the course of radiotherapy (RT). Curcumin, a herbal agent present in Indian spice 'Turmeric' has anti-inflammatory, immunomodulation and wound healing properties. The objective of this pilot randomised controlled clinical trial was to compare the effectiveness and safety of 0.1% curcumin (freshly prepared using nanoparticles) and 0.15% benzydamine mouthwash on RIOM among 74 head and neck cancer patients scheduled to receive RT. Materials and Methods: Assessment of RIOM was carried out using WHO criteria once in a week for 6 weeks. Both modified intention to treat (MIT) and per protocol (PP) analysis were carried out to test the null hypothesis of equal effectiveness on prevention and severity of RIOM. Results: As far as the onset of RIOM is concerned, MIT analysis showed that the instantaneous risk of getting the onset of RIOM was 50% lower (hazard ratio 0.5) in curcumin. Onset of RIOM was also significantly delayed (mean = 19.56, median = 21) in the test group by 2 weeks. But in 'PP' analysis, no significant difference was observed between two preparations and almost all patients experienced the onset. Both the mouthwashes were equally effective in preventing the occurrence of severe form of RIOM in PP analysis after dichotomisation of severity score (≥3 and ≤2). Conclusion: Though both the mouthwashes were not able to completely prevent the onset of RIOM and reduce the severity of RIOM, use of 0.1% curcumin mouthwash was able to significantly delay the onset of RIOM (Clinical trial registration no. CTRI/2018/04/013362).